The role of the mLDL-induced activation of the complement system classical pathway and C3 expression stimulation in atherosclerosis - O M Drapkina (Терапевтический архив, 2018)
The role of modified low density lipoprotein in the activation of the classical pathway of the complement system and increasing expression C3 gene in human macrophages is described, role of these processes on the progression of atherosclerotic vascular lesions is considering.